Analisis Yuridis Pembuktian Kedudukan Ahli Waris atas Harta Warisan Kepemilikan Tanah Adat Batak Toba : (Studi Putusan Mahkamah Agung Nomor 628 PK/PDT/2020) - Ramli Daniel Christian Siregar; Maria Kaban; Utary Maharany Barus (CV Rewang Rencang, 2025)
Inheritance disputes over Batak Toba customary land create legal complexity due to the dualism between customary law and positive law systems, particularly regarding the validity of colonial documents as evidence of ownership. This research examines the concept of heir status, the juridical proof process, and analysis of judicial considerations in Supreme Court Decision Number 628 PK/PDT/2020 using normative juridical methods. The findings show that heir status is based on a patrilineal kinship system with the concept of tunggane ni huta as the highest authority holder. Juridical proof requires a combination of customary evidence (tarombo, hatobangon testimony) and formal documents. The Supreme Court applies an integrative approach recognizing customary legitimacy while meeting formal legal proof standards.